PIERRE ROBIN SEQUENCE: A RARE PRESENTATION OF ABSENT FEMUR AND INGUINAL HERNIA - Faraz, Ahmad; Fareed, Jaweria; Wasay, Hafiz Abdul; Siddique, Ushna Naeem (Journal of Ayub Medical College Abbottabad, 2016)
Pierre Robin Sequence is a well-recognized case of rarity which presents with a traid of glossoptosis, cleft palate. We report a rare case ofPierrerobin Sequence in an Asian child, with the absence of left femur and right sided inguinal hernia. Keywords: Pierre Robin, cleft palate, Absent Femur, inguinal hernia